2017
DOI: 10.1080/01587919.2017.1369006
|View full text |Cite
|
Sign up to set email alerts
|

Refining success and dropout in massive open online courses based on the intention–behavior gap

Abstract: Welten institute -Research centre for Learning, teaching and technology, open university of the netherlands, Heerlen, the netherlands ABSTRACT In this paper we present an alternative typology for determining success and dropout in massive open online courses (MOOCs). This typology takes the perspectives of MOOC-takers into account and is based on the their intentions and subsequent behaviour. An explorative study using two MOOCs was carried out to test the applicability of the typology. Following the tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
78
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 22 publications
5
78
0
3
Order By: Relevance
“…The percentages are quite similar to a recent study, which showed that 5.6-6.5% of the students completed the MOOC, whereas 59-70% of the students achieved their learning objectives (Henderikx et al, 2017). This resulted in a completely distinct picture.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The percentages are quite similar to a recent study, which showed that 5.6-6.5% of the students completed the MOOC, whereas 59-70% of the students achieved their learning objectives (Henderikx et al, 2017). This resulted in a completely distinct picture.…”
Section: Discussionsupporting
confidence: 88%
“…However, not completing an MOOC does not necessarily mean that learning or teaching needs to be improved, because students may have other motivations and learning objectives besides completion (Clow, 2013;Henderikx, Kreijns, & Kalz, 2017;Koller, Ng, Do, & Chen, 2013). However, not completing an MOOC does not necessarily mean that learning or teaching needs to be improved, because students may have other motivations and learning objectives besides completion (Clow, 2013;Henderikx, Kreijns, & Kalz, 2017;Koller, Ng, Do, & Chen, 2013).…”
mentioning
confidence: 99%
“…Insight in these matters is valuable for MOOC-makers as the success measurement is often used as an indicator for the necessity of design interventions [2]. Data of MOOC-II was used to compare currently used certificate-oriented success measurement with our proposed intention-oriented success measurement.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it does not suffice to only look at the number of certificates earned by the MOOC-takers for determining success, even though this method is often transferred from the formal education context to the MOOC and is the most widely-used method of identifying educational success. As an alternative approach, we take the initial intention of the individual as a starting point for measuring success taking into account that MOOCs allow individuals to follow their own learning paths [2]. These intentions may vary from simply browsing through a MOOC to-indeed-getting a certificate.…”
mentioning
confidence: 99%
“…This comes along with a shifted perspective on success in a MOOC: while previous measures mainly accounted for completion rates or certificates earned, modern approaches take user intentions into account and calculate individual goal achievement rates [2,38,39], only with this shift in success measurement, the flipped MOOC is possible: individualizing the learning experience does not necessarily deliver comparable results in terms of completion rates. Consequently, a personalized MOOC would be rated as less successful.…”
Section: Discussionmentioning
confidence: 99%